An Overview of Bibliometric Analysis - Kara Çiğdem, Ayşen Gülçin; Uğraş Dikmen, Asiye; Özkan, Seçil (Turkey Health Literacy Journal, 2024)
Bibliometrics provides the big picture of existing research by analyzing information sets of large volumes of data in a particular field or topic. Bibliometric analyzes aim to summarize a large number of bibliometric data in order to reveal the intellectual structure of publications related to a research field or subject and to present the emerging trends. Relationships between documents, authors, sources, institutions and countries in a research field or subject are examined with bibliometric analysis techniques such as citation, co-citation, joint authorship and bibliographic matching. In this study, it is aimed to give an idea about the steps of bibliometric analysis by providing an overview of bibliometric analysis methods.